The Origins of Liberal Judaism in England The Contribution of Lily H. Montagu - Umansky, Ellen M. (1985)
The Liberal Jewish movement in England owes its inception to Lily H. Montagu, founder of the Jewish Religious Union. Montagu established the J.R.U. in 1902 as an association of Orthodox, Reform and Liberal Jews committed to the revitalization of Anglo-Jewry's religious life. Yet its early commitment to Jewish liberalism, evident in the Union's publications and in the activities that it sponsored, led many to conclude that a schismatic, Liberal Jewish movement was in fact being created. Consequently, by 1909, the Union was renamed the Jewish Religious Union for the Advancement of Liberal Judaism and a fully organized, Liberal Jewish Synagogue was soon established. This essay traces Lily Montagu's contributions to this movement as a religious organizer and leader. Without minimizing the important contributions of either Claude Montefiore, President of the Union, or Israel Mattuck, rabbi of the Liberal Jewish Synagogue, it focuses on the ways in which Lily Montagu, as founder and eventually leader of both the Jewish Religious Union and the World Union for Progressive Judaism, and as lay rabbi of the West Central Liberal Congregation, worked to insure the organizational development of Liberal Judaism in England while reaffirming a commitment to its early spiritual ideals.